Ekstraksi Enzimatik Kitin dan Kitosan dari Limbah Udang - Kristina Novalina Nainggolan (Jurnal Kelautan, Lingkungan, dan Perikanan, 2023)
Chitin is a biopolymer that compiles the shells of insects and crustaceans and the cell walls of fungi, diatoms, bacteria, and algae, while chitosan is chitin derivate. Both of the products have essential roles in various industrial fields. Chitin and chitosan are often produced chemically from shrimp waste (head and the shell). However, chemical residues and poor product characteristics are the weaknesses of this method. Another alternative method is to extract the products enzymatically. Products with better and more specific results and more environmentally friendly processes but have longer processing times at higher costs are the considerations of the enzymatic method. This review focuses on the enzymatic extraction of chitin and chitosan from shrimp shells, including the development and challenges of the process. Chemically and enzymatically, chitin extraction consists of pre-treatment, demineralization, and deproteinization stages, followed by deacetylation to obtain chitosan. Enzymatic shrimp waste demineralization is mainly through a fermentation process using lactic acid bacteria while deproteination with bacteria or protease enzymes. Enzymatic deacetylation of chitin uses enzymes or microbial strains that produce chitin deacetylates. So far, microbial strains or enzyme and fermentation conditions that can extract shrimp waste into chitin with reasonable effectiveness have been found. Moreover, the by-products of enzymatic extraction are rich in high-quality protein, carotenoids (especially astaxanthin), and minerals (especially calcium).